Family Business Transgenerational Continuity in Transition Economies: Towards a Conceptual Model - Štangej, Olga; Škudienė, Vida (Organizations and Markets in Emerging Economies, 2013)
Within classification of emerging economies, Lithuania as part of the former Soviet Union belongs to the group of transition economies. In this paper, we discuss how theorizing leadership succession may contribute to the key strategic questions of succession arising among family businesses in transition economies. The purpose of this study is to revisit the phenomenon of family business succession and linkages among the goals of succession and performance measures of family business. Our study aims at providing three contributions to the current literature. First, it highlights the role of transgenerational continuity of family businesses in transition economies. Second, it revisits the concept of succession through identification of the third – leadership – dimension alongside management and succession. Third, it provides a conceptual model of family business succession outcome measurement and implications for further research.